Effect Of Quality of Service on Loyalty Customers at PT. Pos (Persero) Lubuk Pakam Branch - Irfanni Hutasoit; Sari Wulandari (Journal Of Management Analytical and Solution (JoMAS), 2022)
The purpose of this study was to determine whether there is an influence of service quality on customer loyalty at the Post Office (Persero) Lubuk Pakam Branch ". The data used in this study is primary data with the research instrument in the form of a questionnaire. The population used is 98 customers of the Lubuk Pakam post office using the Slovin formula, and the number of samples is 5000 people per month. The research method used in this research is descriptive quantitative method. The data analysis technique used simple linear regression analysis with the regression equation Y = 8,552 + 748+ e. Partial test results (t) were obtained at 11,158. While the results of the R2 value of 56.5%, so it can be ascertained that the quality of service has a positive and significant effect on customer loyalty and the remaining 43.5% is influenced by other factors.